Pengetahuan Perawat Pelaksana dengan Penerapan Model Asuhan Keperawatan Profesional Penyakit Dalam dan Bedah - Setiawati Setiawati; Lilis Rohayani; Irman Akmaludin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between the knowledge of the implementing nurses and the application of MPKP in the internal medicine and surgery room at Cibabat Hospital, Cimahi City, in 2015. The research method was carried out using a correlational descriptive model approach with a cross-sectional design. The results showed that most respondents had good knowledge, as many as 34 respondents (46.6%). Most of the respondents have been optimal in implementing MPKP 39 respondents (53.4%). In conclusion, there is a significant relationship between the knowledge of implementing nurses regarding MPKP with the optimal application of MPKP carried out by implementing nurses in the room. Keywords: MPKP, Knowledge, Implementing Nurse